In situ construction of dual-morphology ZnCo2O4 for high-performance asymmetric supercapacitors. Issue 8 (2nd July 2019) - Wang, Ziwen; Lu, Shixiang; He, Ge; Lv, Anqi; Shen, Yanmei; Xu, Wenguo
Abstract : The morphologies of ZnCo2 O4 were controlled by an ultrasonic treatment to achieve high-performance supercapacitors. Abstract : In this study, the controllable preparation of ZnCo2 O4 with different morphologies in a reaction system and the orderly weaving of these morphologies into special structures was demonstrated, which might be impossible to achieve using other methods; herein, we successfully prepared a dual-morphology ZnCo2 O4 /N-doped reduced graphene oxide/Ni foam substrate (ZNGN) electrode by ultrasonic processing, a one-step hydrothermal method and a subsequent annealing process for high-performance supercapacitors. At first, ZnCo2 O4 nanosheet orderly formed a honeycomb structure on the surface of Ni foam (NF); this improved the redox surface area of the electrode; then, feather-like ZnCo2 O4 was evenly distributed over the honeycomb structure, playing the role of containment and fixation to provide space for material volume expansion during charging and discharging. The electrochemical test showed that the maximum capacitance of the ZNGN electrode was 1600 F g −1 (960C g −1 ) at the current density of 1 A g −1 in a 6 M KOH solution. Moreover, the asymmetric supercapacitor ZNGN//activated carbon (ZNGN//AC) displayed the excellent energy density of 66.1 W h kg −1 at the power density of 701 W kg −1 . Compared with the capacitance (233.3 F g −1 and 326.6C g −1 ) when ZNGN//AC was fully activated at 4 A g −1, there was almost no loss in capacitance after 2000 charge–discharge cycles, and a 94% capacitance retention was achieved after 5000 cycles. Thus, this excellent electrochemical property highlights the potential application of the dual-morphology ZnCo2 O4 electrode in supercapacitors.